Effectiveness of an inexpensive short-term theoretical-practical course on videosurgery for surgeons in training - Paula Haveroth Takegawa; Jefferson Kalil; Joaquim Murray Bustorff-Silva; Márcio Lopes Miranda (BMC Medical Education, 2022)
Abstract Background The rapid development of video surgery and minimally invasive surgical techniques prompted many studies on the methods of teaching these techniques to young surgeons in training. However, the characteristics of a short-term course that is both easily accessible and efficient for this group of surgeons remain controversial. To investigate this issue, a short-term training method was proposed for first year surgery residents, using inexpensive handmade wooden simulation boxes with the students smartphones as cameras. Its effectiveness was evaluated, as well as possible factors that could influence student performance, such as gender and previous experience with video games. Methods Thirty-six first-year General Surgery residents, entering in 2019 and 2020, participated in the study: 21 were males and 15 were females with ages between 22 and 29 years old, (mean 25.47 years). All participants performed a pre-established exercise (placing two simple stitches using a laparoscopic simulator), which was timed and scored. They then participated in a short theoretical-practical course, consisting of an initial lecture followed by 4 exercises on handcrafted wooden laparoscopic video surgery simulators. Afterwards, they were asked to repeat the same exercise from the first step. Finally, they answered a questionnaire that included questions on previous videogame experience. The data were tabulated and submitted to statistical analysis. Results In the pre-training exercise, 15 (41.66%) participants were able to perform the two simple stitches in the simulator box within the maximum time limit of 5 minutes. After the short course, 22 (61.11%) of participants were able to perform the complete exercise. Improvement in the time to complete the practical exercise was statistically significant (p = 0.0296) after participating in the theoretical-practical course. A better pre- and post-training performance was demonstrated by the 17 participants with experience with video games (p = 0.0116), and a better post-training performance was demonstrated by female participants (p = 0.0405). Conclusion This short-term inexpensive theoretical-practical course in laparoscopic training for surgeons in training was effective in reducing the execution time of a laparoscopic stitch in a simulation box. Previous experience with video games and/or female gender appear to be associated with improved performance.